David Burton: French Colonial Cookery - Jaine, Tom (Petits Propos Culinaires, 2024)
David Burton: French Colonial Cookery: Faber and Faber, London, 2000: ISBN 0-571-19024-3: 260 pp., colour photos, h/b, £17.